Analisis Rantai Nilai Dan Nilai Tambah Kakao Petani Di Kecamatan Paya Bakong Dan Geurudong Pase Kabupaten Aceh Utara - Akhmad Baihaqi; Ahmad Humam Hamid; Romano Romano; Anton Yulianda (Jurnal Agrisep, 2014)
ABSTRACT. The purpose of the study was to determine how the cocoa value chain and add value to the cocoa economy in the supply chain and the Paya Bakong subdistrict, North Aceh District Geurudong Pase. The study population was farmers who joined in cocoa development program by Action Aid and Keumang Foundation 2010-2012, the analysis used is Economic Value Added. The results of the study describes the average cost of production and revenue cocoa plant age 8-9 years is Rp. 2.609 million, - and Rp. 8.228 million, - per hectare per year, with the R / C ratio of 3,05. The average cost per year for the production and revenue of plant age 12-13 years worth Rp 2.827.182,- per hectare with the R / C ratio of 3,96. Value chain that forms at the site of research involving farmers (chain 1), cooperatives, traders or peddlers village, a large village traders (chain 2), secondary cooperatives, districts traders/wholesaler (chain 3), provincial wholesalers / exporters (chain 4) , as well as the industry at home and abroad (chain 5). Value chain created by the farmers - exporters are changes in the value of cocoa into quality classes I, II, III (SNI 01-2323-2000) industry demand. Analysis of Economic Value Added (EVA), Farmers plant age 8-9 years at 3,11 percent, and farmers plant age level 12-13 years gained 3,85 percent. Level of 3,86 percent trader agent, village wholesaler 7,20 percent, district level and wholesalers 5,75 percent. Cooperative farmers obtain the net value added 2,08 percent of each transaction cycle.